THE NOTARY IN AUTHORITY’S MAKING OF HYPOTHEEK - Denny Suwondo; Siti Nurdiyah Fauza Tuanaya (UNISSULA, 2018)
Pursuant to Article 15 paragraph (2) letter (f) of Act No. 2 of 2014 concerning Notary, the Notary as Public Official obtain Attribution of powers in a deed relating to land, including the deed of the Power of Attorney Imposing Mortgage. This study aims to know and understand the authority of the deed Notary Power of Attorn ey Imposing Mortgage. The method used socio - juridical, which inductively began an analysis of the legislation governing the Notary office and encumbrance on land and objects relating to the ground. Research shows that the authorities in deed Notary Power o f Attorney Imposing Mortgage is based on Article 15 (1) of Act No. 4 of 1996 on Mortgage of Land and Their Bodies Relating to dust and Article 15 (2) f of Act No. 2 of 2014 on the Amendment of Act 30 of 2004 on Notary. That in practice the National Land Ag ency of the Republic of Indonesia only receive the Power of Attorney Imposing Mortgage in the form of deed Land Deed Officer.